2022
DOI: 10.1242/jeb.243335
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoxia exposure inhibits larval brain development but does not affect the capacity to mount a cortisol stress response in zebrafish

Abstract: Fish nursery habitats are increasingly hypoxic and the brain is recognized as highly hypoxia-sensitive, yet there is a lack of information on the effects of hypoxia on the development and function of the larval fish brain. Here, we tested the hypothesis that by inhibiting brain development, larval exposure to severe hypoxia has persistent functional effects on the cortisol stress response in zebrafish (Danio rerio). Exposing 5 days post-fertilization (dpf) larvae to 10% dissolved O2 (DO) for 16 h only marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 99 publications
2
5
0
Order By: Relevance
“…As predicted, we observed that offspring derived from parents exposed to diel cycles of heat stress and hypoxia have a reduced endocrine stress response when faced with the same challenge as larval fish. Consistent with the observation that either acute heat stress (36°C for 10 min; Yeh et al, 2013 ) or hypoxia exposure (10% DO for 2 h; Mikloska et al, 2022 ) stimulates the HPI axis in 5 dpf larval zebrafish, we demonstrate that the two stressors combined (36°C and 20% DO for 20 min) elicit an increase in whole body cortisol in control larvae, but has no effect in the larvae derived from parents exposed to cycles of thermal stress and hypoxia. In contrast, the 5 dpf larvae from both parental treatments had a similar increase in whole body cortisol following a swirling stressor, and the magnitude of the response was consistent with a previous observation ( Williams et al, 2017 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As predicted, we observed that offspring derived from parents exposed to diel cycles of heat stress and hypoxia have a reduced endocrine stress response when faced with the same challenge as larval fish. Consistent with the observation that either acute heat stress (36°C for 10 min; Yeh et al, 2013 ) or hypoxia exposure (10% DO for 2 h; Mikloska et al, 2022 ) stimulates the HPI axis in 5 dpf larval zebrafish, we demonstrate that the two stressors combined (36°C and 20% DO for 20 min) elicit an increase in whole body cortisol in control larvae, but has no effect in the larvae derived from parents exposed to cycles of thermal stress and hypoxia. In contrast, the 5 dpf larvae from both parental treatments had a similar increase in whole body cortisol following a swirling stressor, and the magnitude of the response was consistent with a previous observation ( Williams et al, 2017 ).…”
Section: Discussionsupporting
confidence: 88%
“…Together, these results suggest that sustained parental exposure to cycles of thermal stress and hypoxia increase the tolerance of larvae to a similar challenge but does not affect their capacity to mount a cortisol stress response to a novel stressor. Although previous studies using 5 dpf zebrafish larvae have shown that stressors can upregulate hsd11b2 and hsd20b2 expression ( Tokarz et al, 2013 ; Mikloska et al, 2022 ), here we provide novel evidence that acute exposure to combined heat stress and hypoxia also stimulates the expression of both transcripts. Given that hsd11b2 and hsd20b2 expression is cortisol-dependent ( Tokarz et al, 2013 ) and that larvae derived from parents exposed to cycles of thermal stress and hypoxia did not mount a cortisol stress response when challenged with a similar stressor, the finding that larvae from both parental treatments upregulated these transcripts was unexpected.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Adult zebrafish of both sexes were kept in a 60-l glass aquarium with a female and male ratio of 2:1. Adult fish were maintained at a density of 4–5 fish l -1 ( Mikloska et al , 2022 ). The temperature was set at 28°C ± 1°C, and the light/dark cycle was 14:10 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Egg water was replaced twice a day. Neither eggs nor embryos were reared for 12 hours:12 hours in light: dark radiation ( Mikloska et al , 2022 ).…”
Section: Methodsmentioning
confidence: 99%